Intersectionality and the City (Taylor & Francis, 2025)
This book combines intersectional perspectives and urban research to demonstrate the importance of intersectionality as a concept that can complement “refigurational” understandings of social change as the outcome of spatial conflicts. Showing how intersectionality enables us to grasp the intersecting categories of inequality in these spatial tensions, it remains attentive to the role of social difference and power in these processes, as well as to modes of normativity and resistance. With case studies gathered from a range of national contexts, it provides rich empirical insights into the relationship between urban spatialities, power dynamics, and embodied social inequalities, addressing the manner in which different conflicts are made manifest intersectionally in and through situated urban spaces. The chapters consider issues such as the gendering and racialization of urban spaces; urban marginality and environmental pressures; intersectional power dynamics in research; heteronormative and cisgender- centric structures in the city; aging in the city; young people, control, and insecurity; police violence; migrant emplacement and activism; racialized gentrification and commoning, and pandemic safety and protest, to explore the uneven outcomes of spatial planning and urban development. As such, it draws attention to the interplay of various forces in the production of exclusion and injustice and will therefore appeal to scholars of sociology, geography, and urban studies with interests in inequality, social change, and resistance to exclusion.